Desafios para a implantação da Estratégia de Saúde da Família (ESF) em municípios de grande porte: estudo de caso do município de Sorocaba/SP. - Lopes, Rogerio Campos (2017)
Introduction: Initially it was labeled as a program, but due to its specificities, it escapes the usual conception of the other programs conceived in the Ministry of Health, since it is not a vertical intervention and parallel to the activities of traditional health services. Thus, today it is named as Family Health Strategy (ESF). Working in several large municipalities I could see the difficulty that this health policy faces for its consolidation. Objective: To identify the current situation of the ESF in the city of Sorocaba/SP and try to understand the difficulties for its implementation, from its implantation, through its management and maintenance. Methods: This is a descriptive, exploratory and qualitative approach, with proposals for intervention, considering the municipality of Sorocaba/SP as a case study. Documentary data from the Sorocaba Health Department were evaluated and semi-structured interviews were conducted with 6 managers who had or have a central role in defining the health policies of the municipality. Results: The managers pointed out factors that make it difficult to introduce and implement the FHS in the city of Sorocaba, such as insufficient funding, lack of support from the State Department of Health and the Ministry of Health, a constant change of central management, difficulty in inserting processes of solid work and distrust of professionals of the Municipal Health Department. These reports made possible the reflection and the elaboration of practices that can improve this situation. Conclusion: There is a need to change concepts of municipal management to implement the FHS as a model of change in Primary Health Care